Assessing the state anxiety, heart rate responses, and performance during e-bowling game in male and female individuals - Dhirveenraj A/L Raj, Dhirveenraj A/L Raj (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Introduction: Psychological changes is a common situation in a sport performance, including anxiety that may cause changes in other physiological responses. Increased state anxiety can be related to increased heart rate and this could affect performance. In E-sports, anxiety can include repetitive thought loops, especially about things a person cannot complete in the game. The purpose of the present study is to assess the state anxiety, heart rate responses and performance during E-bowling game in male and female individuals. Method: 26 participants were grouped into male group (n = 13) and female group (n = 13). The participants played two games of E-bowling game downloaded in their smartphone. In each game, the participants answered the Revised Competitive State Anxiety Inventory-2 (CSAI-2R) 10 minutes before the E-bowling game starts and recorded their heart rate two minutes before the E-bowling game starts. The performance was recorded as a total score (pin drops) from the two games. Results: There were significant differences in the somatic state anxiety for male and female participants (p=0.025). There were no significant differences in cognitive state anxiety, heart rate and performance between male and female participants. Conclusion: Female participants showed a higher mean score of all the variables compared to male participants during E-bowling game.